2019
DOI: 10.1177/0956797619847164
|View full text |Cite
|
Sign up to set email alerts
|

Schema and Motor-Memory Consolidation

Abstract: Recent research has demonstrated that memory-consolidation processes can be accelerated if newly learned information is consistent with preexisting knowledge. Until now, investigations of this fast integration of new information into memory have focused on the declarative and perceptual systems. We employed a unique manipulation of a motor-sequence-learning paradigm to examine the effect of experimentally acquired memory on the learning of new motor information. Results demonstrate that new information is rapi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 38 publications
3
31
0
Order By: Relevance
“…An explicit bimanual version of the serial reaction time task (SRTT; ( Nissen and Bullemer, 1987 )) previously used in our group ( King et al, 2019 ) that was coded and implemented with the Psychophysics Toolbox in Matlab ( Brainard, 1997 ) was used in this study. Participants were lying in the scanner with a specialized MR-compatible keyboard placed on their lap.…”
Section: Methodsmentioning
confidence: 99%
“…An explicit bimanual version of the serial reaction time task (SRTT; ( Nissen and Bullemer, 1987 )) previously used in our group ( King et al, 2019 ) that was coded and implemented with the Psychophysics Toolbox in Matlab ( Brainard, 1997 ) was used in this study. Participants were lying in the scanner with a specialized MR-compatible keyboard placed on their lap.…”
Section: Methodsmentioning
confidence: 99%
“…In addition to the repeated reactivation-induced strengthening and stabilization of the newly acquired memory trace at the local synaptic level, there is accumulating evidence supporting the existence of a gradual reorganization of temporary formed representations over distributed and long-lasting brain networks (e.g. [73,74]; see also [9,16], for reviews). In accordance with this systems level concept, work from our laboratory looking at procedural memory consolidation has revealed that motor memory traces are not only strengthened during sleep, but undergo qualitative representational changes (e.g.…”
Section: Neural Substrates Associated With Spindlerelated Memory Consolidationmentioning
confidence: 99%
“…Sleep, and specific plasticity-related sleep features such as spindles and slow waves that are present in non-rapid-eye-movement (NREM) sleep, are thought to support declarative schema formation and subsequent integration of novel information [ 1,[11][12][13][14][15][16][17] although see 18 ]. While our previous results hinted that sleep may be crucial for the integration of novel motor information into a previously-acquired schema 7 , the design employed could not differentiate the specific effects of sleep from the influence of time.…”
Section: Introductionmentioning
confidence: 70%